2007
DOI: 10.20396/conex.v5i1.8637981
|View full text |Cite
|
Sign up to set email alerts
|

Dança de salão: uma possibilidade de linguagem

Abstract: ResumoEste estudo tem como objetivo apresentar um olhar sobre a dança de salão de modo que esta atividade possa ser compreendida como uma prática social da linguagem. Para tanto, foram ministradas aulas semanais de dança de salão para crianças (de quinta à oitava série) do Colégio Sistema Positivo da cidade de São José do Rio Preto (SP) num período de três meses. Com base na teoria do Paradigma Indiciário, fizemos uma análise subjetiva das informações coletadas, voltando nossa atenção para sinais discursivos (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ballroom dancing is a physical activity capable of providing these positive changes in older adults (14)(15)(16) . In the study of Borges et al (15) , it was observed that ballroom dancing can contribute to improvements on the balance and functional autonomy of older adults living in long-stay institutions, given that it works by changing the body axis with its different back and forth movements and by shifting the body weight through leading movements.…”
Section: Introductionmentioning
confidence: 99%
“…Ballroom dancing is a physical activity capable of providing these positive changes in older adults (14)(15)(16) . In the study of Borges et al (15) , it was observed that ballroom dancing can contribute to improvements on the balance and functional autonomy of older adults living in long-stay institutions, given that it works by changing the body axis with its different back and forth movements and by shifting the body weight through leading movements.…”
Section: Introductionmentioning
confidence: 99%